Diagnostic Utility of Wireless Video‐Electroencephalography in Unsedated Dogs. (31st July 2017) - James, F.M.K.; Cortez, M.A.; Monteith, G.; Jokinen, T.S.; Sanders, S.; Wielaender, F.; Fischer, A.; Lohi, H.
Abstract : Background: Poor agreement between observers on whether an unusual event is a seizure drives the need for a specific diagnostic tool provided by video‐electroencephalography (video‐EEG) in human pediatric epileptology. Objective: That successful classification of events would be positively associated with increasing EEG recording length and higher event frequency reported before video‐EEG evaluation; that a novel wireless video‐EEG technique would clarify whether unusual behavioral events were seizures in unsedated dogs. Animals: Eighty‐one client‐owned dogs of various breeds undergoing investigation of unusual behavioral events at 4 institutions. Methods: Retrospective case series: evaluation of wireless video‐EEG recordings in unsedated dogs performed at 4 institutions. Results: Electroencephalography achieved/excluded diagnosis of epilepsy in 58 dogs (72%); 25 dogs confirmed with epileptic seizures based on ictal/interictal epileptiform discharges, and 33 dogs with no EEG abnormalities associated with their target events. As reported frequency of the target events decreased (annually, monthly, weekly, daily, hourly, minutes, seconds), EEG was less likely to achieve diagnosis ( P  < 0.001). Every increase in event frequency increased the odds of achieving diagnosis by 2.315 (95% confidence interval: 1.36–4.34). EEG recording length (mean = 3.69 hours, range: 0.17–22.5) was not associated ( P  = 0.2) with the likelihood of achieving a diagnosis. Conclusions and Clinical Importance: Wireless video‐EEG in unsedated dogs had a high success for diagnosis of unusual behavioral events. This technique offered a reliable clinical tool to investigate the epileptic origin of behavioral events in dogs.